Experimental Research on the Stiffness Step between the Main Hull and Superstructure of Cruise Ships - Zhiyong Pei; Bin Yang; Guangwu Liu; Weiguo Wu (Journal of Marine Science and Engineering, 2023)
The demand for larger passenger capacity and more entertainment facilities has led to the rapid growth of the cruise tourism market. The superstructure of cruise ships is designed to be plumper, with numerous decks and complex structural forms. To control the weight and the center of gravity, the bending stiffness of the superstructure is always designed to be weaker than that of the main hull, resulting in a stiffness step. Currently, there is no satisfactory method to accurately estimate the influence of the stiffness step between the main hull and superstructure on the structural response of cruise ships. In the present research, an experimental analysis is conducted to investigate the stiffness step between the main hull and superstructure of a typical cruise ship. By comparing the longitudinal stress distribution characteristics with and without the stiffness step with the theoretical results, the influence of the stiffness step on the longitudinal strength is investigated. Furthermore, the maximum stress and the bending efficiency of the superstructure are also discussed. The present research is of reference significance for the structural safety and reliability design of cruise ships.